Immunophenotypic profile and clinical outcome of monoclonal B‐cell lymphocytosis in kidney transplantation. Issue 8 (26th August 2018) - Alfano, Gaetano; Fontana, Francesco; Colaci, Elisabetta; Franceschini, Erica; Ligabue, Giulia; Messerotti, Andrea; Bettelli, Francesca; Grottola, Antonella; Gennari, William; Potenza, Leonardo; Guaraldi, Giovanni; Mussini, Cristina; et al.
Abstract: Monoclonal B‐cell lymphocytosis (MBL) is a lymphoproliferative disorder characterized by clonal expansion of a B‐cell population in peripheral blood of otherwise healthy subjects. MBL is divided into CLL (chronic lymphocytic leukemia)‐like, atypical CLL‐like and non‐CLL MBL. The aim of this study was to evaluate immunophenotypic characteristics and clinical outcomes of MBL in kidney transplant (KT) recipients. We retrospectively evaluated 593 kidney transplant (KT) recipients in follow‐up at our center. Among them, 157 patients underwent peripheral blood flow cytometry for different clinical indications. A 6‐color panel flow cytometry was used to diagnose MBL. This condition was detected in 5 of 157 KT recipients. Immunophenotypic characterization of MBL showed four cases of non‐CLL MBL and one case of CLL‐like MBL. At presentation, median age was 65 years (range 61‐73). After a median follow‐up of 3.1 years (95%CI; 1.1‐5) from diagnosis, patients did not progress either to CLL or to lymphoma. The disorder did not increase the risk of malignancy, severe infections, graft loss and mortality among our KT recipients. Surprisingly, all cases were also affected by concomitant monoclonal gammopathy of undetermined significance, which did not progress to multiple myeloma during follow‐up. In conclusion, our data suggest that MBL is an age‐related disorder, with non‐CLL MBL being the most common subtype among KT recipients.